Inter‐ and intramolecular electron transfer in copper complexes: electronic entatic state with redox‐active guanidine ligands - Schrempp, David; Leingang, Simone; Schnurr, Martin; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (Chemistry - a European journal, 2017)
Abstract Fast and efficient electron transfer in blue copper proteins is realized by a structural harmonization between the CuI and CuII complex pair (?entatic state? model). Herein, we present now a CuI/CuII complex pair with redox?active guanidine ligands showing almost perfect match between both redox states. By modifying the ligand electron donor strength, the redox chemistry of the copper complex can be controlled to be either metal?centered or to cross the borderline to ligand?centered. This work is the first systematic study of complexes with redox?active ligands within the concept of the entatic state.
Gesehen am 04.04.2018